Advances in Polatuzumab Vedotin-PIIQ Therapy: A Review of Treatment Efficacy in Diffuse Large B Cell Lymphoma and High-Grade B Cell Lymphoma - Abdur Raqib M; Haseeb A; Shafique MA; Fadlalla Ahmed TK; Mustafa MS (Dove Medical Press, 2023)
Moosa Abdur Raqib,1 Abdul Haseeb,2 Muhammad Ashir Shafique,2 Tagwa Kalool Fadlalla Ahmed,3 Muhammad Saqlain Mustafa2 1Department of Medicine, Liaquat College of Medicine & Dentistry, Karachi, Sindh, Pakistan; 2Department of Medicine, Jinnah Sindh Medical University, Karachi, Sindh, Pakistan; 3Department of Medicine, Ahfad University for Women, Omdurman, SudanCorrespondence: Tagwa Kalool Fadlalla Ahmed, Department of Medicine, Ahfad University for Women, Omdurman, Sudan, Tel +249 969710718, Email tagwa.kalool@gmail.comAbstract: Polatuzumab vedotin (PV) is an antibody-drug conjugate that has shown promising results in the treatment of diffuse B-cell lymphoma (DLBCL) and high-grade B-cell lymphoma (HGBCL). This abstract summarizes the current understanding of PV's use in these malignancies based on available clinical data. Multiple clinical trials have evaluated PV as a part of combination therapy regimens in relapsed/refractory DLBCL and HGBCL. The pivotal Phase II study, GO29365, demonstrated that PV in combination with bendamustine and rituximab (BR) significantly improved progression-free survival and overall survival compared to BR alone in patients with relapsed/refractory DLBCL who ineligible for stem cell transplantation were. Subsequently, the US Food and Drug Administration granted accelerated approval to PV in this setting. PV's mechanism of action involves targeting CD79b, a cell surface receptor expressed in B-cell malignancies, and delivering the cytotoxic agent monomethyl auristatin E to CD79b-expressing cells. This approach enhances the selective killing of cancer cells while sparing normal cells. The safety profile of PV is generally manageable, with adverse events including infusion-related reactions, cytopenia, peripheral neuropathy, and infections. Overall, PV has emerged as a valuable treatment option for patients with relapsed/refractory DLBCL and HGBCL, offering improved outcomes when combined with appropriate chemotherapy regimens. Ongoing research and clinical trials are further exploring PV's potential in various treatment settings, including frontline therapy and in combination with other novel agents.Keywords: polatuzumab vedotin, non-Hodgkin lymphoma